Antiproliferative Activity of Neem Leaf Extracts Obtained by a Sequential Pressurized Liquid Extraction - Klebson S. Santos; Andriele M. Barbosa; Victor Freitas; Ana Veruska C. S. Muniz; Marcelo C. Mendonça; Ricardo C. Calhelha; Isabel C. F. R. Ferreira; Elton Franceschi; Francine F. Padilha; Maria Beatriz P. P. Oliveira; Cláudio Dariva (MDPI AG, 2018)
Azadirachta indica A. Juss (neem) extracts have been used in pharmaceutical applications as antitumor agents, due to their terpenes and phenolic compounds. To obtain extracts from neem leaves with potential antiproliferative effect, a sequential process of pressurized liquid extraction was carried out in a fixed bed extractor at 25 °C and 100 bar, using hexane (SH), ethyl acetate (SEA), and ethanol (SE) as solvents. Extractions using only ethanol (EE) was also conducted to compare the characteristics of the fractionated extracts. The results obtained by liquid chromatography-electrospray ionization mass spectrometry suggested a higher concentration of terpenes in the SEA extract in comparison to SH, SE, and EE extracts. Therefore, antiproliferative activity showed that SEA extracts were the most efficient inhibitor to human tumor cells MCF-7, NCI-H460, HeLa, and HepG2. Hepatocellular cells were more resistant to SH, SEA, SE, and EE compared to breast, lung, hepatocellular, and cervical malignant cells. Neem fractioned extracts obtained in the present study seem to be more selective for malignant cells compared to the non-tumor cells.